2009
DOI: 10.1167/9.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Using fMRI to distinguish components of the multiple object tracking task

Abstract: Multiple object tracking (MOT) has proven to be a powerful technique for studying sustained selective attention. However, surprisingly little is known about its underlying neural mechanisms. Previous fMRI investigations have identified several brain areas thought to be involved in MOT, but there were disagreements between the studies, none distinguished between the act of tracking targets and the act of attending targets, and none attempted to determine which of these brain areas interact with each other. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
136
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(157 citation statements)
references
References 41 publications
(73 reference statements)
20
136
0
1
Order By: Relevance
“…Finally, our results provide neuronal correlates of previously reported increases in ERPs and BOLD-signal amplitude during tracking (Culham et al, 1998;Drew et al, 2009;Howe et al, 2009;Doran and Hoffman, 2010). Furthermore, they support behavioral reports linking attention and tracking performance (Yantis, 1992;Sears and Pylyshyn, 2000;Cavanagh and Alvarez, 2005;Tombu and Seiffert, 2008;Iordanescu et al, 2009;Niebergall et al, 2010).…”
Section: Origins Of the Modulatory Signalsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, our results provide neuronal correlates of previously reported increases in ERPs and BOLD-signal amplitude during tracking (Culham et al, 1998;Drew et al, 2009;Howe et al, 2009;Doran and Hoffman, 2010). Furthermore, they support behavioral reports linking attention and tracking performance (Yantis, 1992;Sears and Pylyshyn, 2000;Cavanagh and Alvarez, 2005;Tombu and Seiffert, 2008;Iordanescu et al, 2009;Niebergall et al, 2010).…”
Section: Origins Of the Modulatory Signalsupporting
confidence: 88%
“…A single or multiple moving spotlights of attention may highlight tracked objects and enhance their neuronal representations in visual cortex. Supporting this hypothesis, previous studies of multiple-object tracking (MOT) in humans have demonstrated that visual event-related potentials (ERPs) and BOLD signals evoked by attentively tracked objects are enhanced relative to those evoked by distracters (Culham et al, 1998;Drew et al, 2009;Howe et al, 2009;Doran and Hoffman, 2010). The mechanisms of these effects at the level of single visual neurons remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Using functional MRI in humans, Culham et al (1998) showed that attentive tracking of moving objects activated FEF and the intraparietal sulcus (IPS; the human homologue of LIP) more than twice as much as passive viewing of the same stimuli. Attentional load strongly modulates the activation in IPS but very little in FEF (Culham et al 2001;Jovicich et al 2001;Howe et al 2009;Jahn et al 2012). This difference has been interpreted to suggest that IPS is directly involved in tracking, whereas FEF may perform more general tasks such as the control of eye movements during tracking (Culham et al 2001;Howe et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, at stationary and slow speeds where behavioral performance is at ceiling, perhaps not all the resource is deployed. The uncertainty regarding this point makes it difficult to interpret an fMRI study that contrasted stationary with moving targets (Howe et al, 2009). …”
Section: Discussionmentioning
confidence: 99%